Design of a bimodal didactic unit for the General Pathology course of the Medicine Program of the Decanato de Ciencias de la Salud Universidad Centroccidental Lisandro Alvarado (Boletin Médico de Postgrado, 2023)
Society requires new educational trends in order to respond to the demands of globality in times of uncertainty. We propose the design of a bimodal didactic unit for the General Pathology course of the Medicine Program of the Decanato de Ciencias de la Salud, Universidad Centroccidental Lisandro Alvarado, Barquisimeto, Lara state. The sample was made up of 28 students from the sixth semester of medical school who are studying the General Pathology course. The survey technique was used and the instrument was a structured questionnaire of 27 questions using the Likert scale with the following estimation scale: CA = completely agree, A = agree, PA = partially agree, D = disagree and CD = completely disagree. The results reflected the acceptance of the design (71.4%), contribution to content (67.9%), support of the design (64.3%), usability of digital resources (67.9%), significant learning (57.2%), cognitive content (89.3%), activities (53.6%), strategies (85.7%), practical exercises (42.9%), seminars 32.1% (CA) and 42.9% (A), diagnostic indicator (57.2%), formative (75.4%) and sumative (46.4%). The results show and acceptance and support of the curricular modification of the course, taking into account the update of teaching strategies and educational channels to enhance a meaningful learning.